2007
DOI: 10.1017/s026502150600144x
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1 and A2 receptor agonists reduce endotoxin-induced cellular energy depletion and oedema formation in the lung

Abstract: Adenosine A1- and A2-receptor agonists reduced LPS-induced vasoconstriction and oedema formation by maintenance of tissue energy content. Thus, adenosine receptor stimulation, in particular of the A2 receptor, might be beneficial during acute lung injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 49 publications
(79 reference statements)
3
22
1
Order By: Relevance
“…In an early study, pharmacologic blocking of A1AR attenuated LPS-induced lung injury in cats (24), suggesting a proinflammatory role of A1AR. In two recent studies with rodents, A1AR demonstrated protective effects in models of ischemia reperfusion-and endotoxin-induced lung injury (25,26). Both studies focused on the effects of A1AR on the formation of lung edema and are in line with our findings; leukocyte trafficking, however, was not considered in these studies.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In an early study, pharmacologic blocking of A1AR attenuated LPS-induced lung injury in cats (24), suggesting a proinflammatory role of A1AR. In two recent studies with rodents, A1AR demonstrated protective effects in models of ischemia reperfusion-and endotoxin-induced lung injury (25,26). Both studies focused on the effects of A1AR on the formation of lung edema and are in line with our findings; leukocyte trafficking, however, was not considered in these studies.…”
Section: Discussionsupporting
confidence: 84%
“…In an early study, pharmacologic blocking of A1AR attenuated LPS-induced lung injury in cats (24). In more recent studies, protective effects of A1AR have been demonstrated in models of ischemia reperfusion-and endotoxin-induced lung injury (25,26). In adenosine deaminase (ADA)-deficient mice, which exhibit elevated adenosine levels, genetic removal of the A1AR resulted in enhanced pulmonary inflammation and alveolar destruction (23).…”
mentioning
confidence: 99%
“…To the extent that endothelial mitochondria are responsible for the shedding response, as we show here, loss of mitochondrial function might be proinflammatory. Inflammatory conditions such as sepsis cause loss of lung mitochondrial function, as demonstrated by decreased lung ATP (59,60). Our findings indicate that in such conditions, therapy aimed at restoring endothelial mitochondrial function might protect against the deleterious effects of increasing inflammation.…”
Section: Figurementioning
confidence: 66%
“…LPS caused expression of A 1 , A 2A , and A 2B and P2Y receptors to be increased, and A 3 receptors to be decreased, whereas highvolume ventilation reduced P2Y 4 mRNA levels (Riesenman et al, 2008). On the basis of a study of LPS administration in isolated and ventilated rabbit lungs, it was suggested that adenosine A 2 receptor-mediated stimulation might be beneficial during acute lung injury (Heller et al, 2007). Both A 2A receptors (Reutershan et al, 2007) and A 2B receptors (Eckle et al, 2008) have been claimed to be involved in the attenuation of acute lung injury.…”
Section: Lung Injurymentioning
confidence: 99%